10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
Postmenopausal women (PW) experience hemodynamic and autonomic alterations that increase cardiovascular risk. Although aerobic exercise is widely recognized for its cardioprotective benefits, the chronic effects of resistance training (RT) on cardiovascular and autonomic function in this population remain less established. This systematic review aimed to evaluate the effects of RT on hemodynamic and vascular structure and function, cardiovascular autonomic control, and cardiac structural outcomes in PW. A comprehensive search of PubMed, Scopus, Web of Science, and SPORTDiscus was conducted up to February 2026. Randomized and nonrandomized controlled trials investigating RT interventions (≥4 wk) were included. Primary outcomes were resting heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean blood pressure (MBP). Secondary outcomes included vascular adaptations, heart rate variability (HRV), and cardiac structural characteristics. Meta-analyses were performed using a random-effects model, with pooled effects expressed as Hedges' g; heterogeneity was quantified using I 2 . Risk of bias, reporting quality exercise parameters, and methodological consistency were assessed. Sixty studies met inclusion criteria. Meta-analyses showed statistically significant reductions in HR, SBP, DBP, and MBP after RT. The magnitude of the effects was small for HR (g = 0.30, 95% CI [0.02; 0.58], I 2 = 0.0%) and DBP (g = 0.37, 95% CI [0.11; 0.63], I 2 = 0.0%) and moderate effects for SBP (g = 0.68, 95% CI [0.40; 0.96], I 2 = 0.0%) and MBP (g = 0.68, 95% CI [0.37; 0.99], I 2 = 0.0%). Qualitative synthesis showed modest improvements in vascular adaptations and HRV, whereas echocardiographic studies reported no adverse structural cardiac adaptations. RT produces favorable cardiovascular and autonomic adaptations in PW, improving hemodynamic regulation without structural cardiac alterations.